Gauss-Newton method for convex optimization - Magreñán, Á. Alberto; Argyros, Ioannis K (Contemporary study of iterative methods: convergence, dynamics and applications, 2021)
The goal in this chapter is to present a finer convergence analysis of Gauss–Newton method than in earlier works in order to expand the solvability of convex composite optimizations problems. The convergence of Gauss–Newton method is based on the majorant and center-majorant functions.
Capítulo del libro "Contemporary study of iterative methods: convergence, dynamics and applications"
Keywords: Gauss–Newton method; optimization problems; majorant function; WOS(2)